Glancing angle XRD analysis of particle stability under self-ion irradiation in oxide dispersion strengthened alloys. (1st January 2016) - London, A.J.; Panigrahi, B.K.; Tang, C.C.; Murray, C.; Grovenor, C.R.M.
Graphical abstract: Abstract: We have used glancing-incident angle X-ray diffraction (GIXRD) to study the stability of oxide nanoclusters in an Fe–14Cr–0.2Ti–0.3Y2 O3 ODS alloy. High dose self-ion irradiation produces damaged layers a few hundred nanometres deep normally requiring time-consuming, site-specific techniques to study them. We have shown that GIXRD provides an effective way to study the damage depth profile by varying the incident angle, and that the Y2 Ti2 O7 nanoclusters in these alloys are disrupted by high dose irradiation at temperatures from 150 to 973 K.